Principles of biochemistry / (Acc. D2105) - Voet, Donald (Asia : John Wiley & Sons, Inc., 2008)
Fundamentals of Biochemistry challenges readers to learn the chemical concepts that underlie both classical biochemical theory as well as the latest developments in the field. The third edition combines authoritative biochemical content with an accessible narrative and pedagogic style that greatly enhances learning. It follows a more brief and qualitative approach to present biochemistry with chemical rigor, focusing on the structures of biomolecules, chemical mechanisms, and evolutionary relationships.
Keywords: 1. Biochemistry